Haemodynamic effects of dobutamine in patients with congestive heart failure receiving captopril. - Ikram, H (1981)
Treatment with captopril has proved effective in some patients with resistant heart failure. Since cardiac output responses to captopril treatment are generally small, we infused the positive inotropic agent dobutamine in six patients already receiving captopril to determine whether cardiac output could be augmented without concomitantly increasing myocardial oxygen demands. At low infusion rates of dobutamine (2.5 and 5 microgram/kg per min), a substantial rise in cardiac output was observed yet myocardial oxygen uptake remained well below baseline (pre-captopril/dobutamine) levels. At higher rates of infusion (10 and 20 microgram/kg per min) the rise in cardiac output was accompanied by a pronounced increase in myocardial oxygen uptake, and the appearance of chest pain or multifocal ventricular extrasystoles in three patients. These data indicate that captopril treatment combined with low infusion rates of dobutamine can augment cardiac output in the short term, without increasing myocardial oxygen demand.